(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2015)
The experiment was conducted to study general and specific combining ability (GCA and SCA) and to estimate heterosis estimation at experimental farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during T. Aman, 2006 and 2007 seasons. Eleven rice parental lines consisting of two quasi CMS lines in BC3 generation as lines and nine restorer lines as testers along with their eighteen F1s and a check variety (BRRI dhan37) were used for combining ability study in a line x tester mating design for eight characters. Ratio of general combining ability (GCA) to specific combining ability (SCA) variances above unity were observed for 1000-grain weight(g) indicating predominance of additive gene action for controlling the character. Among mother parents, CMS-1 appeared as good general combiner for panicle length, 1000-grain weight(g), and grain lengthbreadth ratio. Among male parents, Benaful, Oval Tapi and Sorukamini-1 were observed to be good general combiners for most of the characters studied. The cross combinations, CMS-1 × Kataribhog, CMS-2 × Maloti-1 and CMS-2 × Keora were found as good specific combiners for most of the characters under study. Good specific combiners were evolved from all kinds of combinations of general combiners indicating additive and non-additive types of gene effect for inheritance. Maximum hybrids showed desired significant standard heterosis for panicle length and 1000-grain weight. None of the hybrids showed desired and significant standard heterosis simultaneously for any three or more characters.